2004
DOI: 10.1039/b310723j
|View full text |Cite
|
Sign up to set email alerts
|

Blue-shifted lithium bonds

Abstract: A number of lithium bonding systems (X-LiY) have been found in which the X-Li bond is shortened due to the lithium bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 13 publications
4
45
0
1
Order By: Relevance
“…[21] Blue-shifted lithium bonds were evaluated in a number of lithium bonding systems with F 3 CLi or F 3 SiLi molecule as the electron acceptor. [22,23] The singleelectron lithium bonded complexes H 3 C···LiY(Y=H, F, OH, CN, NC, and CCH) were predicted and characterized with theoretical methods. [24] Very recently, we proposed a new kind of lithium bond, [25] in which HMgH acts as the electron donor like that in dihydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Blue-shifted lithium bonds were evaluated in a number of lithium bonding systems with F 3 CLi or F 3 SiLi molecule as the electron acceptor. [22,23] The singleelectron lithium bonded complexes H 3 C···LiY(Y=H, F, OH, CN, NC, and CCH) were predicted and characterized with theoretical methods. [24] Very recently, we proposed a new kind of lithium bond, [25] in which HMgH acts as the electron donor like that in dihydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that for C 4 H 4 O(S)… LiCH 3 system, 21 the C-Li bond is elongated due to the formation of lithium bond, but this bond elongation leads to a blue-shift of the C-Li bond stretching frequency. And Feng et al 16 reported that C-Li bond was contracted with stretching frequency blue-shift in F 3 CLi…C 6 H 6 system. However, in the present study, it can see that for the lithium bond interaction systems, an increase in N(2) -Li(4) bond length may cause a red-shift of its stretching frequency.…”
Section: Geometric Configuration and Frequencymentioning
confidence: 98%
“…It has captured the interest of chemists for a long time and reports about its theory and experiment have been well presented. [1][2][3][4][5][6][7][8][9] It has been found that a lot of physical and chemical phenomena are closely related to the intermolecular weak interactions including hydrogen bond, [10][11][12] π-cation, 13 halogen bond, 8,14,15 lithium bond, 9,16,17 etc. Among these intermolecular interactions studied, hydrogen bond is the earliest and the most extensive one, and lithium-bond is an interesting interaction analogous to hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…It has captured the interest of chemists for a long time and studies about its theory and experiment have been well reported. [1][2][3][4][5][6][7][8][9] It has been found that a lot of physical and chemical phenomena are closely related to the non-covalent intermolecular interactions including hydrogen bond, [10][11][12] π-cation, 13 halogen bond, 8,14,15 lithium bond, 9,16 etc. From a fundamental point of view, the complexes formed by these non-covalent interactions are significant perse, as they bridge the gap between the free molecular systems and the corresponding condensed phases.…”
Section: Introductionmentioning
confidence: 99%